La intervención psicopedagógica - Chiliquinga Toapanta, Andrea Abigail (2016)
This research work is related to "The psycho-pedagogical intervention" in order to achieve the improvement in the academic performance of children attending in this school. The information of the scientific content that allowed us to know everything that was necessary for research, is raised the problem with bases informed, is used methods which helped to describe the project according to the need for school, It is told with the help of teachers, and students, where each provides real facts in the survive was realized to fourth and fifth grade. The idea is to expand the theme of psycho-pedagogical intervention which has received different names: psycho-educational, pedagogical intervention, to refer to a set of activities that contribute to give solution to certain problems prevent others collaborate with them institutions, so the tasks of teaching and education are each time more directed to them needs of them students and the society in general. The psychology is an integrating process and comprehensive is the need to identify possible actions according to the objectives and contexts which are directs; different authors have provided a proposal for principles in the psycho-pedagogical action, this action will enable us to arrive at the solution of the problem, they are shortcomings suffered by children and which affect their academic performance. There is a number of problems that affect the educational environment on children, not only at the regional level and not globally, the project is based on problems affecting homes, day to day family dysfunction one of the major problems that originate from Ecuadorian households, take a large percentage of failures, which does not distinguish social class, or economic status.